Systematic review of structural and functional brain alterations in psychosis of epilepsy. Issue 6 (23rd December 2017) - Allebone, James; Kanaan, Richard; Wilson, Sarah J
Abstract : This systematic review critically assesses structural and functional neuroimaging studies of psychosis of epilepsy (POE). We integrate findings from 18 studies of adults with POE to examine the prevailing view that there is a specific relationship between temporal lobe epilepsy (TLE) and POE, and that mesial temporal lobe pathology is a biomarker for POE. Our results show: (1) conflicting evidence of volumetric change in the hippocampus and amygdala; (2) distributed structural pathology beyond the mesial temporal lobe; and (3) changes in frontotemporal functional network activation. These results provide strong evidence for a revised conceptualisation of POE as disorder of brain networks, and highlight that abnormalities in mesial temporal structures alone are unlikely to account for its neuropathogenesis. Understanding POE as a disease of brain networks has important implications for neuroimaging research and clinical practice. Specifically, we suggest that future neuroimaging studies of POE target structural and functional networks, and that practitioners are vigilant for psychotic symptoms in all epilepsies, not just TLE.